Development and Testing of Down-the-Hole Deployabe X-Ray Florescence Spectrometer - Carter, Geoffrey; Golovanevskiy, Vladimir (SGEM 2010, 2010)
To allow a truly in-situ elemental analysis, an Australian resource company commissioned the development and building of a down-the-hole deployable ED-XRF sensor. The instrument was designed to be deployable up to a depth of 30 m for drill holes of varying diameters as well as being run in a bench-top mode. Following the development and upon commissioning, the ED-XRF system was investigated in the laboratory for its suitability for use in the Iron Ore industry by using well characterised crushed iron ore samples, standards made from analytical reagents and large iron ore rocks that had been sectioned to provide a curved surface for presentation to the XRF. The effects of operating conditions and other parameters were studied using the standards made from the analytical reagents. It was found that the system could be used to determine the elemental Fe content with reasonable accuracy when used on crushed powder samples. The curved surfaces of the sectioned rocks increased the variability of the amount of Fe detected. Two trace elements, Al and Si were also investigated using the same methodology. It was found that the ED-XRF system was not suitable for distinguishing the Al and Si. This paper outlines the ED-XRF system used, the testing methodology employed and the results of the laboratory testing.